ANALYSIS OF THE CAUSES OF DECLINING DEMAND FOR PUBLIC TRANSPORTATION PASSENGERS IN THE CITY OF BANDUNG (Case Study of Trans Metro Bandung Corridor 3 Cicaheum - Sarijadi) - Firyal Wan Azizah; Nurlaela Kumala Dewi; Syafrianita (Journal of Jabar Economic Society Networking Forum, 2025)
Congestion is one of the problems that occur in urban areas, one of which is the city of Bandung. To overcome this problem, the Bandung City Government has established a policy on Trans Metro Bandung with the aim of improving services and providing integrated, safe, fast, smooth, orderly, regular, comfortable, reliable and efficient public transportation. However, in reality, the policy has not been able to achieve the stated goals. This study aims to analyze the causes of the decline in passenger demand for Trans Metro Bandung Corridor 3 (Cicaheum – Sarijadi). The study uses a descriptive quantitative approach by distributing questionnaires to passengers to measure perceptions and expectations of service quality. Data analysis was carried out using the Service Quality (ServQual) method to identify the gap between passenger expectations and perceptions of service quality. The results of the ServQual calculation show a gap value in each dimension, namely, Comfort (-0.47), Regularity (-0.94), Security & Safety (-0.61), Equality (-0.20), and Affordability (-0.62), with a total of -0.58. All of these negative values indicate that the service quality of Trans Metro Bandung Corridor 3 is still below customer expectations.